2021
DOI: 10.1016/j.talanta.2021.122532
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein detection through a plasmonic D-shaped plastic optical fiber aptasensor

Abstract: A specific aptameric sequence has been immobilized on short polyethyleneglycol (PEG) interface on gold nano-film deposited on a D-shaped plastic optical fiber (POFs) probe, and the protein binding has been monitored exploiting the very sensitive surface plasmon resonance (SPR) phenomenon. The receptor-binding domain (RBD) of the SARS-CoV-2 spike glycoprotein has been specifically used to develop an aptasensor. Surface analysis techniques coupled to fluorescence microscopy and plasmonic analysis have been utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 55 publications
1
72
0
Order By: Relevance
“…The specificity and sensitivity of the sensor were demonstrated by testing against different interferences, namely BSA, AH1N1 hemagglutinin protein and MERS spike protein. As a result, an LOD of 37 nM was obtained, which is highly comparable to similar reported optical sensor performances in the literature [78] . In general, the sensitivities of optical sensors were significantly lower than those of electrochemical sensors [87] [85] .…”
Section: Biosensors For the Detection Of Pathogenssupporting
confidence: 89%
See 2 more Smart Citations
“…The specificity and sensitivity of the sensor were demonstrated by testing against different interferences, namely BSA, AH1N1 hemagglutinin protein and MERS spike protein. As a result, an LOD of 37 nM was obtained, which is highly comparable to similar reported optical sensor performances in the literature [78] . In general, the sensitivities of optical sensors were significantly lower than those of electrochemical sensors [87] [85] .…”
Section: Biosensors For the Detection Of Pathogenssupporting
confidence: 89%
“…Several studied investigated optical biosensors for the detection of SARS-CoV-2 [78] [77] . Cennamo et al reported an optical biosensor for the detection of SARS-CoV-2 using DNA sequences [78] .…”
Section: Biosensors For the Detection Of Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…For the clinical cases, the LOD value of the present method was found to be 8.25 × 10 4 copies/mL, whereas ELISA method showed the detection limit of 2.06 × 10 6 copies/mL. Cennamo et al has reported the detection of SARS-CoV-2 spike glycoprotein using a SPR based sensor over D-shaped plastic optical fiber platform [181]. The specific sensing of glycoprotein was achieved using receptor-binding domain (RBD) aptamer of the same SARS-CoV-2 spike glycoprotein target biomolecule.…”
Section: Virus Detectionmentioning
confidence: 72%
“…Cennamo et al also used Song’s aptamers in a plasmonic D-shaped plastic optical fiber aptasensor, achieving a detection limit of 37 nM, but the sensor was not applied to the analysis of real samples. 66 Li et al selected an aptamer against the wild-type and B.1.1.7 spike protein and demonstrated the use of the selected aptamers for the detection of a pseudotyped lentivirus in saliva samples, but again, no real samples from individuals with SARS-CoV-2 were analyzed. 51 In another work, the use of aptamer-functionalized gold nanoparticles was reported, achieving a detection limit of 10 nM, which is equivalent to 3540 genome copies/μL of inactivated SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%